Synthesis and Characterization of Hydroxypropylcellulose from Oil Palm Empty Fruit Bunches (Elaeis guineensis Jacq) - Djagal W. Marseno; Pepita Haryanti; Binardo Adiseno; Haryadi Haryadi (Indonesian Food and Nutrition Progress, 2014)
Indonesia has a lot of oil palm empty fruit bunches (EFB) and usually discarded as agricultural waste. The major component of this oil palm EFB is cellulose, which is useful for food industry in the form of cellulose derivatives such as hydroxypropylcellulose (HPC). This paper reported about a method to prepare HPC from oil palm EFB as cellulose source. Oil palm EFB was dried, cut and milled to obtain EFB powder passed from 60 mesh screen. Cellulose in the EFB powder was extracted using 4% NaOH at 100ºC for 3.5 h, and then bleached using 5% NaOCl at 30ºC for 3 h.  HPC was synthesized from cellulose using NaOH at 5-25% at 25ºC for 1 h, then propylene oxide (PO) at 0.6-1.4 mL per g cellulose was added to the slurry and the temperature was adjusted to 55ºC for 3 h.  HPC from EFB cellulose had more less characters than its commercial especially in purity level. Alkalization using 10% NaOH and its etherification using 1.4% (v/w) PO gave HPC with the highest molar substitution (MS), viscosity, purity and crystallinity i.e. 0.1049; 76.88 cps; 76.91% and 24.39%, respectively.